Komposisi jaringan karkas Domba Ekor Tipis yang diberi Pakan Hijauan pada Periode Akhir Penggemukan - Baihaqi, M.; Rahayu, S.; Duldjaman, M.; Nurmalasari, Nurmalasari (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2013)
The aim of this study was to evaluate the effect of different feeding system on carcass characteristics of Javanese thin-tailed sheep. Nine sheep with average body weight 15.7+1 kg were kept in individual cage and received water ad libitum. The dietary treatments was conducted in three different ratio and periode of concentrate and forage (Brachiaria humidicola) included: 80% forage and 20% concentrate for two months (P1), 20% forage and 80% concentrate for two months (P2) and 20% forage and 80% concentrate for a month followed by 80% forage and 20% concentrate for last month. Data was analysed by analyses of variance (ANOVA). The result showed that there was no significantly effect of treatment on percentage and weight of carcass, commercial cutting of carcass and meat, fat and bone of carcass. The study implicated that sheep fatted by forage for a month of last period could be done by farmer in order to minimize cost production.